The World Council of Churches and Pentecostals. Issue 1 (22nd April 2019) - Robra, Martin
Abstract: This article recalls the history of the relationships between the World Council of Churches (WCC) and Pentecostal churches from the early years of the WCC until today. One of the greatest challenges currently facing the WCC is the shift in focus of Christianity to the South and the East, a phenomenon to which emerging Pentecostal and charismatic churches and communities are contributing. Alongside global cultural trends in the context of globalization, Pentecostal and charismatic piety and spirituality are increasingly affecting the older churches as well. While some see this negatively, many see it as an expression of adaptation to new challenges necessary for the survival of these churches. The article shows how the changing ecclesial context led to the WCC to explore new avenues for building relationships such as a Joint Consultative Group and the Global Christian Forum.